On interactions of massless spin 3 and scalar fields - Lavrov, Peter M. (The European physical journal C)
Using new approach for the deformation procedure in the case of reducible gauge theories (Lavrov in Eur Phys J C 82:429, 2022), it is shown that in the model of massless spin 3 fields and a real scalar field local cubic vertices invariant under initial gauge transformations do not exist while local quartic gauge-invariant vertices can be constructed.